The association between office blood pressure and fluid status using bioimpedance spectroscopy in stable continuous ambulatory peritoneal dialysis patients - Adriaan Slabbert; Mogamat-Yazied Chothia (BMC, 2022)
Abstract Background Hypertension is common in continuous ambulatory peritoneal dialysis (CAPD) patients. It remains to be determined the extent to which fluid overload contributes to uncontrolled blood pressure (BP) in this population. The aim was to determine the association between fluid status as measured using bioimpedance spectroscopy (BIS) and BP in CAPD patients. Methods A cross-sectional study was performed involving 50 stable CAPD patients at a single center in Cape Town, South Africa. All participants were known to have hypertension and were divided into two groups based on office BP measurements: an uncontrolled BP group (systolic BP ≥ 140 mmHg or diastolic BP ≥ 90 mmHg) and a controlled BP group. Fluid status was determined using BIS (Body Composition Monitor®, Fresenius Medical Care, Bad Homburg, Germany). Results There was a statistically significant difference in overhydration (OH) between the uncontrolled BP group and the controlled BP group (3.0 ± 2.3 L vs. 1.4 ± 1.6 L, respectively, P = 0.01). The uncontrolled BP group was older (37.7 ± 9.5 years vs. 32.0 ± 8.0 years, P = 0.04) and had a shorter dialysis vintage (15 [IQR, 7-22] months vs. 31 [IQR, 12-39] months, P = 0.02). Significant correlations were found between OH and the extracellular water (ECW) (r = 0.557, P < 0.01) and ECW to total body water (TBW) ratio (r = 0.474, P < 0.01). Mixed ancestry, presence of residual kidney function, ECW, and ECW to TBW ratio were identified as predictors of OH on multivariable linear regression. Conclusions We found that stable CAPD patients with uncontrolled BP had higher OH compared to patients whose BP was controlled.